Living room design using Kansei Engineering approach with toddler safety aspect - Hanifati, Azizah Nurul; Azmi, Nora; Habyba, Anik Nur (OPSI, 2024)
Toddlers experience physical accidents in the house at a rate of 90 percent. Based on observations, the living room was the most dangerous part of the building compared to other parts. That condition made the parents feel that the safety of their little one was not fully supported. This study aims to design a living room that is safe and comfortable for Toddlers. The design output supports the interior designers in creating a safer Toddler environment. Kansei Engineering guides the identification of living room design for parents looking for their toddlers' safety. The Kansei words gathered from the study are comfortable, multifunction, safe, easy to clean, simple, large capacity, and harmonious. These Kansei words injected into the concept design, which is the harmonious design concept and the simple design concept, by using Principal Component Analysis. The harmonious design has a wood table (X5.1) with a sofa (X7.2) and TV (X9.1) and no flower vase (X11.2) as its decoration, while the simple design has a plastic table (X5.2) with a wood seat (X7.1) and with flower vase (X11.1) but no TV (X9.2). The insights gathered were designed with Blender 3D and integrated with virtual reality Oculus simulation through the SketchFab website.